Evaluation of digital reference services among academic and research libraries in Metro Manila towards the development of digital reference service guidelines for the Philippines - Natividad, Karen Cecille V. (School of Library and Information Studies, University of the Philippines Diliman, 2017)
As the means of communication, socialization, business and other aspects of life continue to change because of the booming technologies and innovations, it is safe to say that the way people access and acquire information also change. From books to CD-ROMs to the Internet as the sources and from in-person to telephone to online as the medium. This has been one of the challenges of reference librarians, being where the clients are. Before, patrons go to the reference desk to inquire. But now, since there are also patrons who prefer to use technology in acquiring information, the reference librarian needs to make sure that she is also there to guide them. Thus, she needs to extend her presence in the online world without leaving her usual desk.